Edukasi Etika Bisnis untuk Pelaku Mikro Kecil Menengah (UMKM) di Kelurahan Kolo Kota Bima - Muhammad Yusuf; Elisa Febrianti; Mariam Mariam; Nurul Aulia (Universitas 45 Surabaya, 2024)
The purpose of this activity is to provide understanding to MSMEs about the importance of ethics in doing business. The educational activities carried out are expected to be able to increase the knowledge of the training participants regarding the importance of ethics in doing business and get to know the basic concepts of entrepreneurship, recognize, find and choose business opportunities, and start a business, and have a creative economy entrepreneurial spirit. The implementation method used is the delivery of material in the form of leaflets or brochures and a question and answer session between the training participants and the person in charge of the training. The material provided includes discussion of: a.) Application of Ethics in doing business for MSME actors, b.) Benefits of Ethics in doing business for MSME actors, c.) Purpose of Ethics in doing business for MSME actors, d.) Application of Ethical Principles in doing business for MSME actors MSMEs.